2019
DOI: 10.1159/000496086
|View full text |Cite
|
Sign up to set email alerts
|

Novel Benzodiazepine-Like Ligands with Various Anxiolytic, Antidepressant, or Pro-Cognitive Profiles

Abstract: Altered gamma-aminobutyric acid (GABA) function is consistently reported in psychiatric disorders, normal aging, and neurodegenerative disorders and reduced function of GABA interneurons is associated with both mood and cognitive symptoms. Benzodiazepines (BZ) have broad anxiolytic, but also sedative, anticonvulsant and amnesic effects, due to nonspecific GABA-A receptor (GABAA-R) targeting. Varying the profile of activity of BZs at GABAA-Rs is predicted to uncover additional therapeutic potential. We synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
124
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(152 citation statements)
references
References 51 publications
(68 reference statements)
15
124
0
1
Order By: Relevance
“…This study was based on the observation that normal aging induces neuronal loss contributing to cognitive decline. Here, we first confirmed that normal aging in mice induces cognitive deficits, with old mice exhibiting impaired working memory in the alternation task, consistent with previous finding (59,63,64). Many compounds (65), drugs (66), natural extracts (64) or physical exercises (67) demonstrated potential at reversing cognitive decline in animal models, but with little-to-no success in human populations (68,69).…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This study was based on the observation that normal aging induces neuronal loss contributing to cognitive decline. Here, we first confirmed that normal aging in mice induces cognitive deficits, with old mice exhibiting impaired working memory in the alternation task, consistent with previous finding (59,63,64). Many compounds (65), drugs (66), natural extracts (64) or physical exercises (67) demonstrated potential at reversing cognitive decline in animal models, but with little-to-no success in human populations (68,69).…”
Section: Discussionsupporting
confidence: 88%
“…The drug was left incubating in the culture for 24 hrs. For the behavioral studies, GL-II-73 was administered through the drinking water at a dose of 30mg/kg/day, for 30 days, based on previous studies from our group (59).…”
Section: Drug Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…CRS. For example, we frequently observe YM deficits in CRS mice 57 , but did not here. To overcome these challenges, we implemented multiple end-point tests assessing top-down behavioral dimensions 131 and used repeatable tests to (a) track the induction of deficits over time, and (b) provide baseline and endpoint readouts to measure the transition into maladaptive behavior (via PCA).…”
Section: Discussionmentioning
confidence: 67%